Does I-Scan Improve Adenoma Detection Rate Compared to High-Definition Colonoscopy? : A Systematic Review and Meta-Analysis - Aziz, Muhammad (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.